GII.17[P17] and GII.8[P8] noroviruses showed different RdRp activities associated with their epidemic characteristics. Issue 1 (26th October 2022) - Gao, Junshan; Zhang, Zilei; Xue, Liang; Li, Ying; Cheng, Tong; Meng, Luobing; Li, Yijing; Cai, Weicheng; Hong, Xiaojing; Zhang, Jumei; Wang, Juan; Chen, Moutong; et al.
Abstract: Norovirus is the primary foodborne pathogenic agent causing viral acute gastroenteritis. It possesses broad genetic diversity and the prevalence of different genotypes varies substantially. However, the differences in RNA‐dependent RNA polymerase (RdRp) activity among different genotypes of noroviruses remain unclear. In this study, the molecular mechanism of RdRp activity difference between the epidemic strain GII.17[P17] and the non‐epidemic strain GII.8[P8] was characterized. By evaluating the evolutionary history of RdRp sequences with Markov Chain Monte Carlo method, the evolution rate of GII.17[P17] variants was higher than that of GII.8[P8] variants (1.22 × 10 −3 nucleotide substitutions/site/year to 9.31 × 10 −4 nucleotide substitutions/site/year, respectively). The enzyme catalytic reaction demonstrated that the Vmax value of GII.17[P17] RdRp was 2.5 times than that of GII.8[P8] RdRp. And the Km of GII.17[P17] and GII.8[P8] RdRp were 0.01 and 0.15 mmol/L, respectively. Then, GII.8[P8] RdRp fragment mutants (A−F) were designed, among which GII.8[P8]‐A/B containing the conserved motif G/F were found to have significant effects on improving RdRp activity. The Km values of GII.8[P8]‐A/B reached 0.07 and 0.06 mmol/L, respectively. And their Vmax values were 1.34 times than that of GII.8[P8] RdRp. In summary, our results suggested that RdRp activities were correlated with their epidemic characteristics. These findings will ultimately provide a better understanding in replication mechanism of noroviruses and development of antiviral drugs.